DAMPAK PENERAPAN IFRS TERHADAP MANAJEMEN LABA DAN KUALITAS PELAPORAN KEUANGAN: BUKTI EMPIRIS CROSS-COUNTRY PADA NEGARA MAJU DAN NEGARA BERKEMBANG - Olivia Gabriella Gunawan; Khairina; Azror Anwar Nasution; Junita Putri Rajana Harahap (Smart Education, 2026)
Abstract: IFRS as a global financial reporting standard is expected to enhance the transparency, relevance, and comparability of accounting information across countries. However, its implementation shows varying outcomes depending on each country’s institutional environment. This study employs a qualitative approach using a library research method by analyzing various international scientific literature, IFRS Foundation reports, and relevant previous studies. The findings indicate that the adoption of IFRS generally reduces earnings management practices by increasing disclosure levels and limiting flexibility in financial reporting. In addition, IFRS contributes to improving financial reporting quality, as reflected by increased relevance and comparability of accounting information. Nevertheless, these effects are not uniform across countries, as they are influenced by institutional factors such as legal system quality, regulatory enforcement effectiveness, and corporate governance practices. Developed countries tend to gain greater benefits from IFRS implementation compared to developing countries. In conclusion, IFRS plays an important role in enhancing global financial reporting quality; however, its effectiveness largely depends on the institutional environment of each country. Therefore, international accounting harmonization should be accompanied by strong regulatory and institutional support to achieve optimal outcomes. Keywords: Earnings Management, Financial Reporting Quality, International Accounting Abstrak: IFRS sebagai standar pelaporan keuangan global diharapkan mampu meningkatkan transparansi, relevansi, dan keterbandingan informasi akuntansi di berbagai negara. Namun, implementasinya menunjukkan hasil yang bervariasi tergantung pada kondisi institusional masing-masing negara. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) melalui analisis berbagai literatur ilmiah internasional, laporan IFRS Foundation, serta hasil penelitian terdahulu yang relevan. Hasil penelitian menunjukkan bahwa penerapan IFRS secara umum mampu menurunkan praktik manajemen laba melalui peningkatan tingkat pengungkapan dan pengurangan fleksibilitas dalam pelaporan keuangan. Selain itu, IFRS juga berkontribusi terhadap peningkatan kualitas pelaporan keuangan yang ditandai dengan meningkatnya relevansi dan keterbandingan informasi akuntansi. Namun demikian, dampak tersebut tidak bersifat seragam di semua negara, karena dipengaruhi oleh faktor institusional seperti kualitas sistem hukum, efektivitas pengawasan, dan tata kelola perusahaan. Negara maju cenderung memperoleh manfaat yang lebih besar dibandingkan negara berkembang dalam implementasi IFRS. Kata Kunci: Manajemen Laba, Kualitas Pelaporan Keuangan, Akuntansi Internasional